Pemikiran Syekh Hasyim Asy'ari tentang Penguatan Pendidikan Karakter Islami di Sekolah Dasar: Systematic Literature Review - Abdul Aziz Binsa; Mohamad Salik (LP2M STAI Darul Kamal NW Kembang Kerang, 2026)
This study examines the relevance of KH. Hasyim Asy'ari's thinking on character education for the context of Elementary Schools/Islamic Elementary Schools (SD/MI) through a Systematic Literature Review (SLR). Analysis of a number of literatures found that Asy'ari's concept of character, which is based on the book